Kepemimpinan Camat dalam Meningkatkan Kinerja Pegawai (Studi pada Kantor Camat Kecamatan Padang Utara Kota Padang) - Hergiansyah, Hergiansyah; Putra, Puji Dwi; Rinaldi, Irvan; Della, Mutia Anno; Devi5, Yasinta (Inovan Publisher, 2025)
The capacity within a person that can influence others at work is the meaning of leadership, which expects to achieve predetermined hierarchical goals. The motivation or purpose behind this study is to determine the leadership of the sub-district head on the performance of employees at the Padang Utara sub-district office, Padang City. This is a qualitative study. The expectation of this research is to improve employee performance by implementing situational leadership theory and combining it with the concept of democratic leadership. This can be seen from the decision-making process in which employees are always involved, delegated authority, control over work, and interactions between leaders and employees. The assessment of employee performance at the office implements an appropriate type of leadership, such as a performance assessment process that gives employees greater responsibility as a sign of trust in their work. In addition, in the Padang Utara sub-district, leaders are required to motivate employees to overcome any obstacles that could have a negative impact on employee performance, both within the agency and outside the agency.